Photosynthetic capacity and water use efficiency in Ricinus communis (L.) under drought stress in semi-humid and semi-arid areas - SANTOS,CLAUDIANA M. DOS (2017)
ABSTRACT Castor bean is one of the crops with potential to provide raw material for production of oils for biodiesel. This species possess adaptive mechanisms for maintaining the water status when subjected to drought stress. A better understanding these mechanisms under field conditions can unravel the survival strategies used by this species. This study aimed to compare the physiological adaptations of Ricinus communis (L.) in two regions with different climates, the semi-arid and semi-humid subject to water stress. The plants showed greater vapor pressure deficit during the driest hours of the day, which contributed to higher values of the leaf temperature and leaf transpiration, however, the VPD(leaf-air) had the greatest effect on plants in the semi-arid region. In both regions, between 12:00 p.m. and 2:00 p.m., the plants presented reduction in the rates of photosynthesis and intracellular CO2 concentration in response to stomatal closure. During the dry season in the semi-arid region, photoinhibition occurred in the leaves of castor bean between 12:00 p.m. and 2:00 p.m. These results suggest that castor bean plants possess compensatory mechanisms for drought tolerance, such as: higher stomatal control and maintenance of photosynthetic capacity, allowing the plant to survive well in soil with low water availability.